Repair of pectus carinatum by a modified Ravitch technique combined with postoperative bracing - Takeshi Shono; Yasutaka Funatsu; Yoshiko Hashimoto; Kumiko Shono (Elsevier, 2018)
A 13-year-old boy with pectus carinatum was successfully treated by modified Ravitch's techniques combined with short-term orthotic bracing. No sternal osteotomy and less extensive resection of costal cartilage were performed. This minimally invasive surgery is safely and effectively in pubertal patients with pectus carinatum. Keywords: Pectus carinatum, Modified Ravitch's techniques, Minimally invasive surgery